Effect of chemical structure of S-nitrosothiols on nitric oxide release mediated by the copper sites of a metal organic framework based environment. Issue 19 (25th April 2017) - Taylor-Edinbyrd, Kiara; Li, Tanping; Kumar, Revati
Abstract : The effect of chemical structure of different biologically compatible S -nitrosothiols on the solvation environment at catalytic copper sites in a metal organic framework (MOF) suspended in a solution of ethanol is probed using computational methods. Abstract : The effect of chemical structure of different biologically compatible S -nitrosothiols on the solvation environment at catalytic copper sites in a metal organic framework (MOF) suspended in a solution of ethanol is probed using computational methods. The use of a copper based MOF as a storage vehicle and catalyst (copper sites of the MOF) in the controlled and sustained release of chemically stored nitric oxide (NO) from S -nitrosocysteine has been shown to occur both experimentally and computationally [ J. Am. Chem. Soc., 2012, 134, 3330–3333; Phys. Chem. Chem. Phys., 2015, 17, 23403]. Previous studies on a copper based MOF, namely HKUST-1, concluded that modifications in the R-group of s -nitrosothiols and/or organic linkers of MOFs led to a method capable of modulating NO release. In order to test the hypothesis that larger R-groups slow down NO release, four different RSNOs (R = cysteine, N -acetylcysteine, N -acetyl-d, l -penicillamine or glutathione) of varying size were investigated, which in turn required the use of a larger copper based MOF. Due to its desirable copper centers and more extensive framework, MOF-143, an analog of HKUST-1 was chosen to further explore both the effect of different RSNOs as well as MOF environments on NO release. Condensed phase classical molecular dynamics simulations are utilized to study the effect of the complex MOF environment as well as the chemical structure and size of the RSNO on the species on the catalytic reaction. The results indicate that in addition to the size of the RSNO species and the organic linkers within the MOF, the reaction rates can be modulated by the molecular structure of the RSNO and furthermore combining different RSNO species can also be used to tune the rate of NO release.